DOCTORAL STUDENT OF THE KARAKALPAK INSTITUTE OF AGRICULTURE AND AGROTECHNOLOGIES - ORAZIMBETOV EDILBEK KAYPBEKOVICH (TADQIQOTLAR, 2025)
ABSTRACT The cultivation of pumpkin (Cucurbita L) in the agro-climatic conditions of Karakalpakstan holds significant potential due to the crop’s adaptability, drought resistance, and economic value. This study investigates the optimal agrotechnological practices for growing pumpkin in arid and semi-arid regions of Karakalpakstan, focusing on soil preparation, irrigation regimes, planting densities, fertilization systems, and disease resistance. Field trials were conducted over two growing seasons to evaluate the yield, fruit quality, and resistance to abiotic stress factors such as salinity and high temperatures. The results demonstrate that the use of drip irrigation, organic mulching, and biofertilizers significantly enhances productivity and fruit quality. Furthermore, locally adapted pumpkin varieties showed better resilience to environmental stressors compared to introduced cultivars. The findings provide a scientific basis for developing sustainable pumpkin production systems in resource- limited regions, contributing to food security and the diversification of agricultural production in Karakalpakstan.